Protector effect of beta-glucans from shrimp pond-related yeasts in Penaeus vannamei rearing under white spot syndrome virus presence - Ochoa-Álvarez,Norma A. (Pontificia Universidad Católica de Valparaíso. Facultad de Recursos Naturales. Escuela de Ciencias del Mar, 2021)
ABSTRACT This research study tested the protective effect of prolonged exposure of shrimp food supplemented with glucans from shrimp-pond related yeasts on shrimp Penaeus vannamei reared under the presence of the white spot syndrome virus (WSSV). The glucans extracted and purified from isolated marine yeasts identified as Debaryomyces hansenii, Candida tropicalis, Candida humilis, Candida glabrata, Pichia kudriavzevyi, Wickerhamomyces anomalus and the terrestrial Saccharomyces cerevisiae yeast were characterized by the Fourier-transform infrared spectroscopy and proton nuclear magnetic resonance spectroscopy. The treatments were prepared with food enriched with the yeast beta-glucans and the control groups without beta-glucans. Shrimp were fed thrice a day and challenged orally with WSSV on days 31, 54, 66 and muscularly at day 70. The animals were assessed for the protective effect in terms of post-infection total hemocyte counts, and survival rate. The results indicated that marine yeasts possessed ß-1,3/1,6-glucans, and that D. hansenii was an excellent source yielding 30% of its dry biomass of pure glucans. For the positive control group where no glucans were added, WSSV challenges showed 100% survival when the virus was provided orally, and 40% when the virus was injected. These results also indicated that the shrimp line selected for this study was a resistant line for WSSV. Shrimp groups fed with glucans of the marine yeasts D. hansenii and C. humillis showed a significant protection, allowing shrimp survival of 66% while terrestrial yeast showed 57.14%. These results indicated that marine yeasts growing in the shrimp pond were an excellent source of beta-glucans that allowed extra protection against the mortality caused by this pathogenic virus.